2022
DOI: 10.3390/insects13070582
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Transglutaminase Genes TGase2 and TGase3 Has Infection-Dependent Effects on the Heart Rate of the Mosquito Anopheles gambiae

Abstract: Transglutaminases are pleiotropic enzymes that in mosquitoes participate in the formation of the mating plug and the wound-induced antimalarial response. Moreover, one transglutaminase, TGase3, negatively regulates the infection-induced aggregation of hemocytes on the heart. Given that TGase3 is an inhibitor of periostial hemocyte aggregation, we used RNAi-based gene silencing followed by intravital video imaging to scrutinize whether any of the three transglutaminases encoded in the genome of the mosquito, An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The IMD pathway also induces the expression of the thioester containing protein TEP1 , which is involved in phagocytosis and periostial hemocyte aggregation (14). Moreover, transglutaminases are pleiotropic enzymes that in Drosophila inhibit the IMD pathway (38, 39), and a mosquito transglutaminase – TGase3 – negatively regulates periostial hemocyte aggregation and has infection-dependent effects on the heart rate (40, 41). Finally, the JNK pathway is associated with cell adhesion and phagocytosis by regulating the cytoskeleton (32, 42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMD pathway also induces the expression of the thioester containing protein TEP1 , which is involved in phagocytosis and periostial hemocyte aggregation (14). Moreover, transglutaminases are pleiotropic enzymes that in Drosophila inhibit the IMD pathway (38, 39), and a mosquito transglutaminase – TGase3 – negatively regulates periostial hemocyte aggregation and has infection-dependent effects on the heart rate (40, 41). Finally, the JNK pathway is associated with cell adhesion and phagocytosis by regulating the cytoskeleton (32, 42).…”
Section: Resultsmentioning
confidence: 99%
“…We recently tested whether transglutaminases are involved in periostial responses in A. gambiae , and found that TGase3 – but not TGase1 or TGase2 – negatively regulates periostial hemocyte aggregation during the early stages of infection and the sequestration of melanin by periostial hemocytes during the later stages of infection (40). Moreover, disrupting TGase2 and TGase3 has infection-dependent effects on the heart rate (41). Combined, these data further support our conclusion that the IMD pathway is a positive driver of heart-associated immune responses (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The IMD pathway also induces the expression of the thioester containing protein TEP1 , which is involved in phagocytosis and periostial haemocyte aggregation [14]. Moreover, transglutaminases are pleiotropic enzymes that in Drosophila inhibit the IMD pathway [38,39], and a mosquito transglutaminase— TGase3 —negatively regulates periostial haemocyte aggregation and has infection-dependent effects on the heart rate [40,41]. Finally, the JNK pathway is associated with cell adhesion and phagocytosis by regulating the cytoskeleton [32,42].…”
Section: Resultsmentioning
confidence: 99%
“…We recently tested whether transglutaminases are involved in periostial responses in A. gambiae , and found that TGase3 —but not TGase1 or TGase2 —negatively regulates periostial haemocyte aggregation during the early stages of infection and the sequestration of melanin by periostial haemocytes during the later stages of infection [40]. Moreover, disrupting TGase2 and TGase3 has infection-dependent effects on the heart rate [41]. Combined, these data further support our conclusion that the IMD pathway is a positive driver of heart-associated immune responses (figure 6).…”
Section: Discussionmentioning
confidence: 99%